Sustainability Apps – The Key to Promoting Sustainable Shopping? - Anna-Katharina Jäger; Anja Weber; Manfred Kirchgeorg (Marketing Review St.Gallen, 2020)
Consumers increasingly express the desire to buy more sustainable goods, but they can hardly assess which products are actually "green". Mobile apps could assist shoppers at the point of sale to select the most environmentally sustainable products, for instance by comparing products or providing additional information. Our user-centric qualitative research provides first insights on how such an app should be designed to overcome purchase barriers. Furthermore, we test the influence of the developed sustainability app on consumers' purchase intention and decision certainty in an experimental study.
Keywords: 650